Designing Standard Growth Chart Based on Weight-For-Age Z-Score of Children in East Java Using Least-Square Spline Estimator - Nur Chamidah; Ardi Kurniawan; Toha Saifudin (Contemporary Mathematics and Applications (ConMathA), 2022)
Children would be categorized as children who have underweight nutritional status, if according to index of anthropometric they have a lack of weight. In Indonesia, this anthropometric index is recorded on a Card Toward Health called as KMS. This card follows the WHO-2005 standard which is designed based on samples from Brazil, Ghana, India, Norway, Oman, and USA. Those samples, of course, physically are very different from Indonesian children. Therefore, in this paper we design weight-for-age Z-score standard growth charts of children by using least-square spline estimator and samples of children from East Java province, Indonesia. Next, the proposed children standard growth charts are used to assess East Java children nutritional status. The results show that the proposed standard growth charts have met the goodness of fit criteria namely the average values of coefficient determination for boy and girl are close to one, and values of mean square errors are close to zero. It means that the proposed growth charts are more suitable to be used to assess the nutritional status of East Java children, because they can better explain the real conditions of children in East Java, Indonesia than the WHO-2005 standard growth charts.